Social and spatial effects on genetic variation between foraging flocks in a wild bird population - Radersma, R; Garroway, C; Santure, A; De Cauwer, I; Farine, D; Slate, J; Sheldon, B (John Wiley & Sons Ltd, 2017)
Social interactions are rarely random. In some instances animals exhibit homophily or heterophily, the tendency to interact with similar or dissimilar conspecifics respectively. Genetic homophily and heterophily influence the evolutionary dynamics of populations, because they potentially affect sexual and social selection. Here we investigate the link between social interactions and allele frequencies in foraging flocks of great tits (Parus major) over three consecutive years. We constructed co-occurrence networks which explicitly described the splitting and merging of 85,602 flocks through time (fission-fusion dynamics), at 60 feeding sites. Of the 1711 birds in those flocks we genotyped 962 individuals at 4701 autosomal single- nucleotide polymorphisms (SNPs). By combining genome-wide genotyping with repeated field observations of the same individuals we were able to investigate links between social structure and allele frequencies at a much finer scale than was previously possible. We explicitly accounted for potential spatial effects underlying genetic structure at the population level. We modelled social structure and spatial configuration of great tit fission-fusion dynamics with eigenvector maps. Variance partitioning revealed that allele frequencies were strongly affected by group fidelity (explaining 27-45% of variance) as individuals tended to maintain associations with the same conspecifics. These conspecifics were genetically more dissimilar than expected, shown by genome-wide heterophily for pure social (i.e. space-independent) grouping preferences. Genome-wide homophily was linked to spatial configuration, indicating spatial segregation of genotypes. We did not find evidence for homophily or heterophily for putative socially relevant candidate genes or any other SNP markers. Together, these results demonstrate the importance of distinguishing social and spatial processes in determining population structure.